(untitled) (South East Asia Journal of Public Health, 2018)
Major proportion (40-70%) of neonatal mortality is among ‘term neonates’. Even though, information on neonatal outcomes of term neonates is scarce. The high volume of term neonatal admissions to neonatal care units signify the importance of studying the neonatal outcomes among term neonates. The aim of this study is to describe the neonatal outcomes, of term neonates following term deliveries (37 completed weeks - 41 completed weeks and 6 days) at Teaching Hospital (TH) Kandy, Sri Lanka. A descriptive cross-sectional study was conducted to describe neonatal outcomes of term neonates before the initial hospital discharge point. A sample of 1,105 neonates, delivered at term were studied during the study period. Mean gestational age at delivery is 38.85 weeks and 41% of term neonates are delivered before completion of 39 weeks of Period of Amenorrhoea (POA). The mean birth weight of the term neo-nates is 2925.24 grams. Out of all term neonates, 15.84% (n=175) were admitted to Neonatal Care Unit (NCU) and 23.3% (n=257) had at least one diagnosed neonatal condition. The commonest neonatal condition was bacterial sepsis of newborn (n=138, 12.48%), followed by neonatal jaundice from other and unspecified causes (n=84, 7.6%), and respiratory distress of newborn (n=44, 3.94%). Median hospital stay of term neonates is 3 days. Majority of term neo-nates admitted to NCU are normal weight term neonates. Nearly one-fourth of term neonates had at least one diag-nosed neonatal condition. Prevention and control of infection from the time of birth to the time of discharge from the hospital should be given due attention to reducing bacterial sepsis among term neonates. South East Asia Journal of Public Health Vol.7(2) 2017: 34-39